Witnesses in Cyberbullying: Roles and Dilemmas. Issue 1 (4th January 2021) - Pepler, Debra; Mishna, Faye; Doucet, Jeremy; Lameiro, Melanie
: This study explored youths' perceptions of the nature and dilemmas of being a bystander in cyberbullying. Although there are many benefits of peer interactions through social media, there are risks, including cyberbullying. Bystanders are integral in the dynamics and harm in both face-to-face and cyberbullying. Using a qualitative approach, authors share youth voices on the experience of witnessing cyberbullying and the dilemmas they face in deciding whether and how to respond to support a peer. Authors conducted thematic analysis of qualitative interviews with 16 adolescents. Youths described a range of feelings experienced by witnesses, from discomfort and anger to moral disengagement and justification for cyberbullying. Youths reported three forms of bystander roles: outsider, assistant, and defender, consistent with traditional bullying. The dilemmas they faced in witnessing and intervening that emerged were consistent with the five stages of bystander decision making. Youths indicated that the solutions for cyberbullying rest on the shoulders of adults.